Independent association between serum C‐peptide levels and fat mass‐to‐lean mass ratio in the aging process. Issue 7 (20th September 2014) - Li, Ying; Zheng, Lian Shun; Li, Yue; Zhao, Duo Duo; Meng, Lu
<x xml:space="preserve">Abstract</x> Aim The changes in body composition and biomarker levels that occur during the aging process are complex and remain poorly understood. The present study aimed to evaluate changes in serum C‐peptide levels and fat mass‐to‐lean mass ratio (FM/LM ratio) with increasing age, and to explore the associations between serum C‐peptide levels and FM/LM ratio. Methods This was a population‐based cross‐sectional study that included 3912 participants aged 30–85 years. Body composition was measured using dual‐energy X‐ray absorptiometry. Analysis of covariance was used to evaluate how the serum C‐peptide level and FM/LM ratio change with increasing age, as well as how the FM/LM ratio changes in line with increasing serum C‐peptide level. A multiple linear regression analysis was carried out to determine the association between serum C‐peptide level and FM/LM ratio. Results Analysis of covariance showed that serum C‐peptide levels, and most regional FM/LM ratios tended to increase in line with increasing age. Total fat mass, total lean mass, percentage total fat mass and total FM/LM ratio were significantly elevated, and percentage total lean mass decreased significantly with increasing serum C‐peptide levels in both men and women. Multiple linear regression analysis showed that serum C‐peptide level was strongly associated with the total FM/LM ratio. Conclusions The findings showed that both serum C‐peptide level and FM/LM ratio increased with increasing age, and the serum C‐peptide level was closely associated with changes in the total FM/LM ratio. Geriatr Gerontol Int 2015; 15: 918–926.